COGNITIVE BEHAVIOURAL THERAPY VS STANDARDISED MEDICAL CARE FOR ADULTS WITH DISSOCIATIVE NON-EPILEPTIC SEIZURES (CODES): AN RCT PROTOCOL. Issue 9 (13th August 2015) - Goldstein, LH; Chalder, T; Carson, AJ; Landau, S; McCrone, P; Magill, N; Medford, N; Murray, J; Reuber, M; Richardson, M; Stone, J; Mellers, JDC
Abstract : Objective: Our overall aim is to evaluate the clinical and cost effectiveness of specifically adapted Cognitive Behavioural Therapy (CBT) (plus Standardised Medical Care – SMC) in comparison to SMC alone for outpatients with dissociative seizures (DS), within a pragmatic, multi-centre UK-based RCT. This will redress the limited evidence base for psychotherapy in this patient group. Method: Adults with DS but without currently active epilepsy will receive their diagnosis and information from a neurologist/epilepsy specialist and their seizure occurrence will be monitored. Three months post diagnosis they will be reviewed by a psychiatrist with interest and expertise in DS who will represent the diagnosis and deliver an information leaflet. Those continuing to experience DS in the previous 8 weeks and meeting other inclusion criteria will, if willing, be consented, undergo baseline assessments and be randomised to receive either 12 sessions of CBT (plus a booster session) as well as SMC or SMC alone. We aim to randomise 298 patients (149 to each arm). DS frequency will be monitored fortnightly and follow-ups will occur at 6 and 12 months post randomisation. An intention to treat analysis will evaluate effectiveness in outcomes relating to seizure frequency severity and freedom, mood and psychological state, quality of life and health service use. A qualitative study will investigate participants' experiences of the interventions and barriers to participation that might affect subsequent implementation in the NHS. Results: Multiple sites in England, Wales and Scotland have been enlisted. Recruitment in neurology clinics has commenced. Training for service user advisors, research workers and CBT therapists has been delivered. Conclusion: The design and progress will be described. This is the largest planned trial for patients with DS to date. See ISRCTN05681227 for further details. FUNDING: NIHR HTA reference 12/26/01.